Cascading impacts of a climate-driven ecosystem transition intensifies population vulnerabilities and fishery collapse - Rogers-Bennett, Laura; Catton, Cynthia A. (Frontiers in Climate, 2022)
The recent large-scale intensification of marine heatwaves, and other climate-related stressors, has dramatically impacted biogenic habitats around the globe, including marine ecosystems such as coral reefs, fringing mangrove, seagrasses, and kelp forests. While the impacts to foundation species may be of particular concern, these ecological catastrophes underscore the need to examine how whole systems respond to a suite of stressors. The recent climate-driven collapse of the bull kelp forest and recreational red abalone fishery in northern California provides an example of unanticipated ripple and lagged effects in the system, intensifying vulnerabilities and accelerating population and fishery collapse. For this case study, we examined fifteen years (2003-2018) of biological survey data on the bull kelp forest ecosystem – before, during, and after an extreme climate event. We document the interactions and complexity of impacts over time, as well as the resulting increased vulnerability of red abalone to additional anthropogenic, biological, and environmental stressors. We observed progressively stronger population-level responses of the red abalone to the marine heatwave and the regional loss of kelp, driving the movement of adults and juveniles in search of food. As food remained scarce, we documented the loss of productivity with diminished gonad and body condition, the absence of larval or newly-settled abalone, mass mortalities, and shoreward shifts in depth distributions. With 40% of the population dead or dying, juvenile and trophy-sized abalone abandoning cryptic habitats, the shift in the distribution to shallower depths increased the vulnerability of red abalone to the fishery. Other anthropogenic, biological, and climate-related stressors that disproportionately impact shallow habitats are now a growing concern for the survivors. For red abalone, previously unanticipated cascading risks include increased wave energy, warming air temperatures, freshwater flooding, landslides, as well as possible oil spills and harmful algal blooms. Climate-driven changes in vulnerability to fishing and environmental stressors present significant challenges for sustainable natural resource management in dynamic stressed systems, and underscore the need for continued system-focused monitoring. We present a conceptual framework supporting similar ecosystem investigations of recent and future climate impacts to inform adaptive ecosystem-based management strategies.